Paleoecology and paleoenvironments of Podocarp trees in the Ameghino Petrified forest (Golfo San Jorge Basin, Patagonia, Argentina) : Constraints for early Paleogene paleoclimate - Brea, Mariana (2011)
During the Early Paleocene (Danian), Central Patagonia had a warm-temperate climate and was dominated by evergreen coniferous forests. Abundant permineralized conifer woods along with some dicot and palm leaf compressions were found in the Ameghino Petrified Forest, and provide evidence of this type of flora. All the permineralized wood and large trunks recovered were assigned to the species Podocarpoxylon mazzonii. An estimated tree height of 17-29m was calculated on the basis of diameter measurements. Based on 14 ring sequences, with a total of 169 rings, the mean ring width and Mean Sensitivity (MS) were 1.23 and 0.19mm respectively. The growth rings are moderately wide, extremely uniform and complacent, indicating that the environment was favourable and constant, and lacked significant stress factors limiting tree growth. Following the quantitative analysis for conifers outlined by Falcon-Lang, the growth ring anatomy of the Podocarpoxylon mazzonii suggests that these trees had an evergreen habit. The combination of the fossil flora, growth ring, and sedimentological analyses suggest that this mostly evergreen coniferous forest developed under warm-temperate conditions and without limiting factors.